2022
DOI: 10.3389/fsurg.2022.894775
|View full text |Cite
|
Sign up to set email alerts
|

Application Status and Prospects of Artificial Intelligence in Peptic Ulcers

Abstract: Peptic ulcer (PU) is a common and frequently occurring disease. Although PU seriously threatens the lives and health of global residents, the applications of artificial intelligence (AI) have strongly promoted diversification and modernization in the diagnosis and treatment of PU. This minireview elaborates on the research progress of AI in the field of PU, from PU’s pathogenic factor Helicobacter pylori (Hp) infection, diagnosis and differential diagnosis, to its management and complications (bleeding, obstru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…With people’s increasing attention to healthy diet and the popularization of Helicobacter pylori (Hp) eradicating treatment, the incidence and mortality of gastric cancer in European and American countries have been significantly reduced in recent years, ranking after the tenth among all tumors ( 1 ). However, gastric cancer is still a heavy burden in East Asian countries such as China, Japan and South Korea ( 2 ). Noteworthily, early gastric cancer (EGC) has a desirable prognosis compared with advanced gastric cancer (AGC).…”
Section: Introductionmentioning
confidence: 99%
“…With people’s increasing attention to healthy diet and the popularization of Helicobacter pylori (Hp) eradicating treatment, the incidence and mortality of gastric cancer in European and American countries have been significantly reduced in recent years, ranking after the tenth among all tumors ( 1 ). However, gastric cancer is still a heavy burden in East Asian countries such as China, Japan and South Korea ( 2 ). Noteworthily, early gastric cancer (EGC) has a desirable prognosis compared with advanced gastric cancer (AGC).…”
Section: Introductionmentioning
confidence: 99%
“…It is most common in the mucosa of the gastrointestinal tract, particularly the stomach and duodenum, which secrete gastric acid. As many as 5 percent to 10 percent of people in the general population have a lifetime prevalence of PU of 0.1 percent to 0.3 percent (Zhao et al, 2022). As a result, early detection and prevention of PU are critical to reducing the health care costs of the global population.…”
Section: Introductionmentioning
confidence: 99%
“…Artificial intelligence, however, is here to stay, and it is crucial that the future development of AI in surgery is directed by the needs of surgeons and patient groups. Studies have shown that machine learning may improve clinical decision-making in complex cases with multiple comorbidities ( 7 , 8 ). In any domain where pattern recognition is required, machine learning algorithms may help provide more accurate predictions of treatment outcome.…”
mentioning
confidence: 99%